Formation and Transfer of Multi-Species Biofilms Containing E. coli O103:H2 on Food Contact Surfaces to Beef - Nan, Yuchen; Rodas-Gonzalez, Argenis; Stanford, Kim; Nadon, Celine; Yang, Xianqin; McAllister, Tim; Narváez-Bravo, Claudia (Frontiers in Microbiology, 2022)
Interactions of Shiga toxin–producing E. coli (STEC; O103:H2) with lactic acid bacteria (LAB) or spoilage bacteria (SP) multispecies biofilms on polyurethane (TPU) and stainless-steel (SS) were assessed at 10 and 25°C under wet and dry conditions after 6, 30, and 60 days of storage. One LAB T1: Carnobacterium piscicola + Lactobacillus bulgaricus, and two SP T2: Comamonas koreensis + Raoultella terrigena; T3: Pseudomonas aeruginosa + C. koreensis were assessed for their ability to form multispecies biofilms with O103:H2. O103:H2 single-species biofilms served as a control positive (T4). Coupons were stored dry (20–50% relative humidity; RH) or moist (60–90% RH) for up to 60 days, at which point O103:H2 transfer to beef and survival was evaluated. At 25°C, T3 decreased beef contamination with O103:H2 by 2.54 log10 CFU/g (P < 0.001). Overall, at 25°C contamination of beef with O103:H2 decreased (P < 0.001) from 3.17 log10 CFU/g on Day 6 to 0.62 log10 CFU/g on Day 60. With 60 days dry biofilms on TPU, an antagonistic interaction was observed among O103:H2 and multispecies biofilm T1 and T3. E. coli O103:H2 was not recovered from T1 and T3 after 60 days but it was recovered (33%) from T2 and T4 dry biofilms. At 10°C, contamination of beef with O103:H2 decreased (P < 0.001) from 1.38 log10 CFU/g after 6 days to 0.47 log10 CFU/g after 60 days. At 10°C, recovery of O103:H2 from 60 days dry biofilms could only be detected after enrichment and was always higher for T2 than T4 biofilms. Regardless of temperature, the transfer of O103:H2 to beef from the biofilm on TPU was greater (P < 0.001) than SS. Moist biofilms also resulted in greater (P < 0.001) cell transfer to beef than dry biofilms at 10 and 25°C. Development of SP or LAB multispecies biofilms with O103:H2 can either increase or diminish the likelihood of beef contamination. Environmental conditions such as humidity, contact surface type, as well as biofilm aging all can influence the risk of beef being contaminated by STEC within multi-species biofilms attached to food contact surfaces.